A potential role of microRNAs in plant response to metal toxicity - Yang, Z.M.; Chen, J.
MicroRNAs (miRNAs)regulate plant growth and development by silencing gene expression at post-transcriptional level. Recent studies have shown that miRNAs are the regulators of plant response to environmental stresses. Also, genome-wide profiling of small RNAs reveals that many miRNAs are in response to heavy metals. Identification of the targets of metal-regulated miRNAs demonstrated that most of the target genes are involved in diverse metabolic pathways including sulphate allocation and assimilation, phytohormone signalling, antioxidation, and miRNA biogenesis. Thus, the high-throughput sequencing of small RNAs provides a powerful tool for mining a number of known and unknown miRNAs in plants in response to metal stress. Here, we discuss recent studies focusing on the newly identified miRNAs and their potential targets in plants and propose a new scenario involving plant tolerance to metal toxicity as part of the dynamic network that defines the potential roles of miRNAs in plant adaptation to heavy metal stress.